Evaluasi Strategi Kesehatan Berbasis Masyarakat dalam Penanganan Stunting di Puskesmas Dander Kapubaten Bojonegoro - Lukito, Cahya; Septian, Esa; Nurhidayah, Laila (Riwayat: Educational Journal of History and Humanities, 2025)
program at Puskesmas Dander and analyze the factors influencing its success. The research uses a qualitative descriptive approach, with data collection through semi-structured interviews, non-participant observation, and documentation. The informants consist of healthcare workers at Puskesmas Dander and community members involved in the stunting program. Data were analyzed using the Miles and Huberman interactive analysis method, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the stunting prevention program at Puskesmas Dander, which includes nutritional education for pregnant women, exclusive breastfeeding, and Supplementary Feeding Program (PMT) for toddlers, has successfully reduced the stunting rate by 0.1% between 2022 and 2023. However, challenges remain, including low public awareness, economic constraints, and limited participation in socialization efforts. The implications of this study emphasize the importance of a multisectoral approach and collaboration between the health, education, and economic sectors in reducing stunting. Furthermore, increased community participation through more intensive training and socialization is crucial to achieving greater success in reducing stunting in the regions.